Thor, Love and Thunder: Sebuah Easter Egg tentang Pergeseran Kebudayaan dan Kepercayaan Eropa Pra-Reformasi Gereja - Musdodi Manalu (Collecta: Jurnal Teologi dan Tradisi Kristen, 2024)
This article explores the influence of Christianity on European culture through a historical lens, focusing on its impact as reflected in contemporary media, particularly within the Marvel Cinematic Universe (MCU). The study aims to examine the relationship between European religious history and the portrayal of certain characters in the MCU, with specific attention to Thor: Love and Thunder. Like many Hollywood films, the MCU contains references and underlying messages that viewers often overlook. The findings reveal that the MCU implicitly portrays elements of European cultural history through key characters, reflecting an interpretation that intertwines historical religious understanding with the syncretism that characterized the cultural struggles and awakenings of Europe.